A cross country analysis of social justice in assessment - Poskitt JM; Adie L; Hayward L (Massey University, 2017)
Social justice is an international concern and evident in education and assessment policies, but is less evident in the enactment of reporting policy and practices. We explore these ruptures in assessment policy through analysis of the assessment documents of three countries, Australia, New Zealand and Scotland. Specifically, we address the social and cultural assumptions that limit opportunities for student and parent voice in reporting processes. Robinson and Taylor’s (2007) four core values of student voice form the conceptual framework. In order to better align assessment, reporting and social justice practices, we draw on notions of spirit and letter of assessment, feedback to create dialogic spaces, and the relationship between formative and summative assessment. Lundy’s (2007) conceptualisation of voice is used to propose ways forward to create a more socially just reporting system. To transform reporting practices, we recommend reconceptualising reporting as communicating, and assessment as progressing learning.
Keywords: assessment policy; social justice; reporting; student voice; parents